Superconducting properties of (NH3)yLixFeSe0.5Te0.5 under pressure - Xiaofan Yang; Tong He; Tomoya Taguchi; Huan Li; Yanan Wang; Hidenori Goto; Ritsuko Eguchi; Takafumi Miyazaki; Hitoshi Yamaoka; Hirofumi Ishii; Yen-Fa Liao; Yoshihiro Kubozono (New Journal of Physics, 2019)
We prepared two superconducting phases of (NH _3 ) _y Li _x FeSe _0.5 Te _0.5 , which show superconducting transition temperatures ( T _c ’s) as high as 20.2 and 29.5 K at ambient pressure, here called the ‘low- T _c phase’ and ‘high- T _c phase’. The temperature dependence of electrical resistance ( R ) was measured for the low- T _c phase of (NH _3 ) _y Li _x FeSe _0.5 Te _0.5 over a pressure ( p ) range of 0–14 GPa, and for the high- T _c phase of (NH _3 ) _y Li _x FeSe _0.5 Te _0.5 over 0–19 GPa, yielding double-dome superconducting T _c – p phase diagrams, i.e. two superconducting phases (SC-I and SC-II) were found for both the low- T _c and high- T _c phases under pressure. For the low- T _c phase, the maximum T _c was 20.2 K at 0 GPa for SC-I, and 19.9 K at 8.98 GPa for SC-II. For the high- T _c phase, the maximum T _c was 33.0 K at 1.00 GPa for SC-I, and 24.0 K at 11.5–13.2 GPa for SC-II. These results imply that the maximum T _c value of the high pressure phase (SC-II) does not exceed the maximum value of the SC-I, unlike what was shown in the T _c – p phase diagrams of (NH _3 ) _y Li _x FeSe and (NH _3 ) _y Cs _x FeSe investigated previously. Nevertheless, the double-dome T _c – p phase diagram was found in metal-doped FeSe _0.5 Te _0.5 , indicating that this feature is universal in metal-doped FeSe _1− _z Te _z . Moreover, no structural phase transitions were observed for either the low- T _c or high- T _c phases of (NH _3 ) _y Li _x FeSe _0.5 Te _0.5 over the wide pressure range of 0–15.3 GPa, and the T _c -lattice constant ( c ) plots for both phases were recorded to determine the critical point separating SC-I and SC-II.